Long-term efficacy and safety of guselkumab in Chinese patients with moderate-to-severe plaque psoriasis - Zheng, Jianfeng; Chen, Wenjuan; Yi, Xuemei; Yu, Ning; Ding, Yangfeng; Gao, Yunlu (Frontiers in Medicine, 2023)
Background Randomized controlled trials indicated guselkumab, the first anti-interleukin-23 monoclonal antibody, is efficacious in plaque psoriasis. However, guselkumab's performance in real life is scarcely examined, especially in China. Objectives This work aimed to assess the long-term effectiveness of guselkumab in actual clinical practice in China. Methods A retrospective study was performed for plaque psoriasis cases administered guselkumab in Shanghai Skin Disease Hospital between January 2020 and September 2022. Results A total of 37 patients were included (29 men, 78.4%), with a mean follow-up period of 72.3 ± 26.7 weeks (range of 12–108 weeks). At baseline, clinical examination revealed a mean PASI of 12.3 ± 7.1, a mean BSA of 17.1 ± 18.1, and a mean DLQI of 7.7 ± 4.3. Twenty-two (62.9%) and 17 (48.6%) cases achieved PASI 90 and PASI 100 responses at week 28. From weeks 60 to 92, >80% of cases achieved PASI 90 and PASI 100 responses. Regarding safety, no cases of serious AEs were recorded. A total of nine cases (24.3%) had different abnormal results in HBV markers, and two were T-SPOT positive. There was no hepatitis B virus or tuberculosis outbreak in these patients. Conclusion This real-life study confirmed the long-term efficacy and safety of guselkumab in daily clinical practice.